Supporting real-time awareness for the community of runners. (19th July 2010) - Gotoda, Naka; Matsuura, Kenji; Hirano, Takuji; Tanaka, Toshio; , Yoneo Yano
This paper describes a training-support environment for runners who run together with mobile sensor network. The system provides awareness information as feedbacks to runners by using their kinetic feature and communication conditions between sensors at the real-time. In particular 3D-acceleration sensor catches repeats of arm swing. Moreover, sensors transmit such information to the remote server on the web. The remote advisor can observe the condition of runners by way of graphic reports of sensing information on the web and control the trigger of awareness manually. We have designed and implemented our proposal. From the result of a trial use, the system contributes some runners' improvements about the stabilisation of their pace.